A shooting method for a nonlinear beam equation - Amster, Pablo Gustavo (2008)
We study the existence of solutions for a nonlinear fourth-order ODE with nonlinear boundary condition that arises in beam theory. Using a shooting type argument, we prove the existence of at least one solution of the problem.